Atmospheres of breathing - Škof, Lenart, 1972-; Berndtson, Petri (Albany, NY : SUNY Press, 2018)
Attempts to think anew about philosophical questions from the perspective of breath and breathing. As a physiological or biological matter, breath is mostly considered to be mechanical and thoughtless. By expanding on the insights of many religions and therapeutic practices, which emphasize the cultivation of breath, the contributors argue that breath should be understood as fundamentally and comprehensively intertwined with human life and experience. Various dimensions of the respiratory world are referred to as "atmospheres" that encircle and connect human existence, coexistence, and the world.
Introduction -- I. Philosophical atmospheres of breathing. Logos and psyche : a hermeneutics of breathing -- The possibility of a new respiratory ontology -- Breath as a way of self-affection : on new topologies of transcendence and self-transcendence -- Aesthetics of breathing : some reflections -- II. Philosophical traditions of breathing. The breathing of the air : pre-socratic echoes in Levinas -- Mindfulness of breathing in early Buddhism -- Inspiration and expiration : yoga practice through Merleau-Ponty's phenomenology of the body --The concept of Qi in Chinese philosophy : a vital force of cosmic and human breath -- Phenomenology of the wind and the possibility of preventive medicine : a discussion of Ki (wind) following Kaibara Ekiken (1630-1713) -- III. Voices and media of breathing. "Thoughts that breathe" -- Theater of breath : an Artaud-Derrida existential conflict -- The media of breathing -- IV. Breathful and breathless worlds. The politics of breathing : knowledge on air and respiration -- Breath as the hinge of dis-ease and healing -- Invisible suffering : the experience of breathlessness -- Feminist politics of breathing -- Postface. The commonwealth of breath.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 23, 2018).
eBooks on EBSCOhost
Keywords: Respiration -- Miscellanea; Respiration -- Religious aspects; Respiration -- Miscellanées.; Respiration -- Aspect religieux; HEALTH & FITNESS -- Healthy Living; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Preventive Medicine; Respiration; Respiration -- Religious aspects; Trivia and miscellanea